2004
DOI: 10.1038/sj.jp.7211065
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight by Gestational Age and Sex at a Rural Referral Center

Abstract: Determine the distribution of birthweights in singleton births by gestational age and gender at Marquette General Hospital, a rural referral center in Michigan's upper peninsula. STUDY DESIGN:Birth log data were examined for prenatal factors and obstetrical outcomes. The birthweight distribution was compared to published values, and a linear regression model of prenatal factors was developed. RESULTS:Our median birthweights were significantly greater than published values. Males were 128 g heavier than female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Although likely to be less precise than maternal reports or measured birthweight, lower self-reported birthweight was associated with female sex, increased deprivation index, multiple births and self-reported maternal smoking. These associations were not only in the expected direction, but demonstrated effect sizes which have been demonstrated in other studies with more accurate birthweight data available 19 , 20 . This is in keeping with a recent study of 541 individuals where a positive correlation was observed between self-reported birthweight in the Million Women Study and their recorded birthweight in 1946, as part of the MRC National Survey of Health and Development birth cohort 21 …”
Section: Discussionsupporting
confidence: 89%
“…Although likely to be less precise than maternal reports or measured birthweight, lower self-reported birthweight was associated with female sex, increased deprivation index, multiple births and self-reported maternal smoking. These associations were not only in the expected direction, but demonstrated effect sizes which have been demonstrated in other studies with more accurate birthweight data available 19 , 20 . This is in keeping with a recent study of 541 individuals where a positive correlation was observed between self-reported birthweight in the Million Women Study and their recorded birthweight in 1946, as part of the MRC National Survey of Health and Development birth cohort 21 …”
Section: Discussionsupporting
confidence: 89%
“…Infant size was bigger for the male term followed by female term, male preterm and female preterm. Many literature also found this kind of interaction effect on birth size [38].…”
Section: Discussionmentioning
confidence: 73%
“…The babies averaged 39.6 (SD = 1.1) weeks gestational age, birthweight of 3536 (SD = 460) grams, length of 49.9 (SD = 2.5) centimeters, and head circumference of 34.4 (SD = 1.7) centimeters. A review of 2098 infants born at our facility from 1999 through 2001 found that 95.19% were Caucasian, 2.43% Native American, 1.00% mixed race, 0.86% African American, 0.33% Hispanic, and 0.19% Asian American[11]. No shift in the racial/ethnic characteristics of this population has occurred in the intervening years.…”
Section: Resultsmentioning
confidence: 99%